2004
DOI: 10.1007/s00059-004-2574-4
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Current Treatment Options of In-Stent Restenosis

Abstract: Coronary stent implantation is currently performed in > 80% of percutaneous coronary interventions. Its main late complication is the development of in-stent restenosis (ISR), occurring in 10-80% of lesions treated in daily practice. The classification by Mehran et al. is most commonly used. Current therapeutic options to treat ISR include repeat balloon angioplasty, repeat stenting, cutting balloon angioplasty, directional coronary atherectomy, rotational coronary atherectomy, brachytherapy, and drug-eluting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Coronary stent implantation is currently performed in more than 80% of percutaneous coronary interventions. 76 Stenting, which involves implanting a metallic mesh to increase blood flow, is rapidly becoming the preferred technique for the percutaneous treatment of coronary artery disease, since it has significant advantages over angioplasty, the mechanical alteration of narrowed or totally obstructed blood vessels. 77 Stents prevent vessel closure and early vessel recoil and improve the long-term patency of arteries.…”
Section: Integrated Microbial Cellulose: In Vivo Tissue-engineering Amentioning
confidence: 99%
“…Coronary stent implantation is currently performed in more than 80% of percutaneous coronary interventions. 76 Stenting, which involves implanting a metallic mesh to increase blood flow, is rapidly becoming the preferred technique for the percutaneous treatment of coronary artery disease, since it has significant advantages over angioplasty, the mechanical alteration of narrowed or totally obstructed blood vessels. 77 Stents prevent vessel closure and early vessel recoil and improve the long-term patency of arteries.…”
Section: Integrated Microbial Cellulose: In Vivo Tissue-engineering Amentioning
confidence: 99%
“…Paclitaxel binds to microtubules and stabilizes microtubule assembly, inhibiting cell cycles that are dependent on microtubular turnover. It inhibits the proliferation and migration of vascular smooth muscle cells (95). The TAXUS IV trial confirmed the effectiveness of paclitaxel-coated stents on in-stent stenosis reported in earlier trials (96).…”
Section: Desmentioning
confidence: 52%
“…In addition, most drug-eluting stents are currently available only for cardiac applications. Other options to treat in-stent restenosis have been reported [9], one being intravascular radiation called brachytherapy, in which special catheters are used to apply radiation to diseased sites to destroy in-stent tissue. Although this approach has been successful in limiting restenosis [10], various practical issues related to the safety and the needs for special facilities prevent its widespread application [11].…”
mentioning
confidence: 99%
“…Other mechanical techniques that use catheters equipped with cutting tools (cutting balloons, rotational atherectomy, etc.) to remove restenotic lesions have been reported [9]. However, their use is limited mainly due to their inherent risk of vessel perforation.…”
mentioning
confidence: 99%
See 1 more Smart Citation